Preformed Crowns - A Successful Approach to Restore Primary Teeth - Bahar, Iqbal; Quader, SM Abdul; Khan, Md Ali Afzal; Jahan, KM Rawnak; Khan, Md Asif Iqbal (Update Dental College Journal, 2013)
Preformed crowns are indicated for restoring severely decayed/ pulpally treated primary teeth since early1940s. Although the composition of Preformed Crowns varies from manufacturer to manufacturer, the preparation of teeth and manipulation technique for seating of Preformed Crowns (PC) on primary teeth would not invite much disagreement among different authors and operators. Available literature readily accepts that when used with a proper cementing agent such as Resin-Modified Glass Ionomer (RMGI) luting cement, preformed crown remain a superior and durable treatment option for primary teeth. This review article supports using preformed crowns for restoring critically damaged primary teeth until a suitable alternative is available. DOI: http://dx.doi.org/10.3329/updcj.v1i2.13984 Update Dent. Coll. j. 2011: 1(2): 29-34